2015
DOI: 10.5014/ajot.2015.014373
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Intention to Use a Virtual Instrumental Activities of Daily Living System Among People With Stroke

Abstract: OBJECTIVE. The purpose of this study was to investigate the behavioral intention to use (BIU) regarding a virtual system for practicing instrumental activities of daily living (IADLs) among people with stroke.METHOD. Fourteen people who had sustained a stroke used a virtual world-based system over four sessions to participate in virtual occupations of preparing meals and putting away groceries. To investigate intention to use the technology, participants responded to a questionnaire based on the Technology Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The majority of studies found that tele-neurorehabilitation interventions were not inferior to conventional center-based models of care ( 41 , 42 , 46 , 47 , 50 , 54 56 , 60 ). Patients and carers/family reported subjective improvements in communication, gait, activities of daily living, and motivation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies found that tele-neurorehabilitation interventions were not inferior to conventional center-based models of care ( 41 , 42 , 46 , 47 , 50 , 54 56 , 60 ). Patients and carers/family reported subjective improvements in communication, gait, activities of daily living, and motivation.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies found that participants enjoyed gaming technology associated with some of the tele-neurorehabilitation interventions and found them easy to use, engaging and motivating ( 41 , 43 , 47 , 48 , 52 , 54 ). Experiences with both hardware and software had a marked effect on the user perception of tele-neurorehabilitation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of stroke patients after the stroke period treatment improves with technological devices, particularly for upper limb and hand recovery. 17 19 …”
Section: Introductionmentioning
confidence: 99%
“…Home rehabilitation technology solutions have tremendous potential in supporting the short-term and long-term performance of plans of care for motor cognitive rehabilitation in a highly engaging environment, thus empowering the patient, increasing their motivation, positive compliance with the therapy, and improved quality of life. [17][18][19] Such benefits are particularly important for post-stroke patients, especially those in the chronic phase who are typically affected by mobility problems (sometimes associated with different levels of depressions), complicating their travel to clinics in order to attend rehabilitation programs. 14 TR can be a suitable alternative to conventional rehabilitation care for post-stroke patients, especially in remote or underserved areas, because many patients have reduced access to care due to limited regional and logistic resources.…”
mentioning
confidence: 99%